Tender Loving Care: A Conceptual Analysis - Kumiko Kido; Akemi Mitani; Yuko Uemura (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2023)
Background: Studies have shown that combining tender loving care (TLC) with the treatment of patients with recurrent miscarriages can improve pregnancy outcomes. The importance of TLC has long been recognised in studies on psychiatric, gerontological, and end-of-life nursing in Western countries. Recently, randomised controlled trials (RCTs) have been used to examine the improvement in outcomes with the addition of TLC to the treatment of patients with recurrent miscarriages; however, no conclusions have been reached. TLC is a highly beneficial and harmless intervention that is not necessary for conducting RCTs. Therefore, healthcare professionals need to be aware of exercising TLC when treating patients with recurrent miscarriages. However, the concept of TLC is ambiguous and its definition is unclear. Purpose: This study aimed to conduct a conceptual analysis of TLC and clarify its constructs. Clarifying the definition of TLC will provide professionals with basic information that will be helpful when exercising TLC with patients who experienced repeated miscarriages despite of hopes of having a baby. Methods: This study was conducted using Walker and Avant’s concept analysis approach. Research published between the first edition of the journal till January 2022 were searched, and the titles and abstracts of the studies were reviewed to determine their suitability. Consequently, 28 articles, all of which were in English, were selected for conceptual analysis. The were CINAHL Plus with Full Text and MEDLINE databases were examined. The search term used was ‘tender loving care’. Results: The results of the conceptual analysis of TLC revealed the following antecedents, defining attributes, and consequences. The antecedents involve patients with the following diseases or disabilities: (1) suffering from mental or physical distress, (2) facing significant barriers in life (illness, disability, etc.), and (3) being unable to manage their mental health and well-being through self-care. Conclusion: In this study, a conceptual analysis of TLC was conducted using Walker and Avant's (2000) method. As a result of the conceptual analysis, ‘tender loving care’ was defined as ‘the care for mentally or physically distressed or impaired subjects by health professionals, parents, and teachers based on compassion and empathy, who perceive the condition of the subject and respond appropriately, thereby reducing tension, distress, and anxiety and achieving a state of mental and physical well-being’.